Breaking the Cycle: Legal Counseling for Drug Rehabilitation in Lido, Indonesia - Silalahi, Fernando; Tampubolon, Manotar; Nadapdap, Binoto (Lebah, 2025)
Drug abuse continues to be a major concern that affects both individuals and society as a whole. In response, the Indonesian government has adopted a rehabilitative approach for drug users, as detailed in the Narcotics Law. Legal counseling is a vital component of this strategy, providing recidivists with essential knowledge about their rights and responsibilities during the rehabilitation process, especially at the Narcotics and Drug Rehabilitation Center (NARKOBA) in Lido, Sukabumi. These counseling sessions feature presentations on narcotics laws, the rehabilitation process, and interactive discussions to engage participants effectively. The success of legal counseling is evident in participant feedback, with 95% indicating a greater understanding of rehabilitation laws and increased confidence in their reintegration, while only 5% express uncertainty about their future. To evaluate its effectiveness, pre- and post-counseling interviews assess participants' understanding. This initiative not only promotes legal awareness and encourages active participation in rehabilitation but also helps to diminish the stigma surrounding drug rehabilitation, supporting a comprehensive approach to recovery